Behavior analysts can be interdisciplinary too: A review of Durand's Autism Spectrum Disorder. Issue 4 (17th October 2014) - Smith, Tristram
Abstract V. Mark Durand's (2013) book, Autism Spectrum Disorder: A Clinical Guide for General Practitioners, eases readers into the vast scientific literature on individuals with autism spectrum disorder (ASD), encourages behavior analysts to examine our place in this literature, and illustrates how we might communicate effectively with a general audience. Durand shows that we have developed many beneficial interventions for individuals with ASD yet may harbor obsolete views about what ASD is. Moreover, his description of ASD suggests that we should consider expanding our range of treatment targets and serve a broader segment of the ASD population. He also shows that investigators in disciplines outside applied behavior analysis (ABA) have contributed to understanding the causes and characteristics of ASD. Thus, rather than focusing mainly on ABA, Durand portrays ABA as one of many disciplines engaged in productive research on ASD; this portrayal may be both accurate and effective as a communication strategy.